2013
DOI: 10.1111/jcmm.12098
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ silencing enhances osteogenic differentiation of human adipose‐derived mesenchymal stem cells

Abstract: Peroxisome proliferator-activated receptor gamma (PPARγ) is the master regulator of adipogenesis, and has been indicated as a potential therapeutic target to promote osteoblast differentiation. However, recent studies suggest that suppression of PPARγ inhibits adipogenesis, but does not promote osteogenic differentiation in human bone marrow-derived mesenchymal stem cells (hBMSCs). It was reasoned that the osteogenic effect of PPARγ suppression may be masked by the strong osteogenesis-inducing condition common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 19 publications
3
26
0
Order By: Relevance
“…The optimal bFGF was determined as 10 ng in the present study, similar to the previous report [14]. PPARγ is known as a potential target for regulating the osteogenic differentiation of progenitor cells, and suppression of PPARγ by RNA interference was demonstrated to promote osteogenic differentiation of human MSCs [2]. However, siRNA transfection with conventional method was usually transitory (within one week).…”
Section: Alp Activity and Calcium Contentsupporting
confidence: 82%
See 3 more Smart Citations
“…The optimal bFGF was determined as 10 ng in the present study, similar to the previous report [14]. PPARγ is known as a potential target for regulating the osteogenic differentiation of progenitor cells, and suppression of PPARγ by RNA interference was demonstrated to promote osteogenic differentiation of human MSCs [2]. However, siRNA transfection with conventional method was usually transitory (within one week).…”
Section: Alp Activity and Calcium Contentsupporting
confidence: 82%
“…It has been demonstrated that down-regulation of PPARγ could significantly promote bone regeneration [18]. In a report by Lee et al [2], suppression of PPARγ through RNA interference efficiently enhanced MSC osteogenic differentiation induced by osteogenic medium, suggesting that suppressing PPARγ by siRNA may be a potent enhancer for MSC osteogenic differentiation.…”
Section: Bfgf and Sirna Releasementioning
confidence: 99%
See 2 more Smart Citations
“…PPAR-γ plays a critical role in commitment switch of progenitor cells between adipogenesis and osteogenesis [36,37]. It has been reported that PPAR-γ silencing increases osteogenic differentiation of hADSCs [38]. We observed that the treatment of TNF-α restored the BMP2-induced increase in osteogenic differentiation in hADSCs in which the addition of BMP2 alone inhibited osteogenic differentiation, which results from TNF-α-induced inhibition of PPAR-γ and C/EBP-α expression.…”
Section: Discussionmentioning
confidence: 99%